HCMV Envelope Glycoprotein Diversity Demystified - Foglierini, Mathilde; Marcandalli, Jessica; Perez, Laurent (Frontiers in Microbiology, 2019)
Human cytomegalovirus (HCMV) is the viral leading cause of congenital birth defects and is responsible for important morbidity and mortality in immunosuppressed individuals. Considerable efforts were deployed in the last decade to develop a vaccine capable of preventing HCMV infection. However, in recent clinical trials, vaccines showed at best modest efficacy in preventing infection. These findings might be explained by the high level of sequence polymorphism at the genomic level. To investigate if genomic variation also leads to antigenic variation, we performed a bioinformatic sequence analysis and evaluated the percentage of conservation at the amino acid level of all the proteins present in the virion envelope. Using more than two hundred sequences per envelope glycoprotein and analyzing their degree of conservation, we observe that antigenic variation is in large part limited to three proteins. In addition, we demonstrate that the two leading vaccine candidates, the pentamer and gB complexes, are well conserved at the amino acid level. These results suggest that despite genomic polymorphism, antigenic variability is not involved in the modest efficacy observed in the recent clinical trials for an HCMV vaccine. We therefore propose that next generation vaccines should focus on stabilizing and refining the gB domains needed to induce a protective humoral response.